Noise induced hearing loss among quarry workers in Kelantan - Aziah, Daud (Pusat Pengajian Sains Perubatan, 2012)
Introduction: Noise is one of the environmental and occupational hazards listed in the Factory and Machinery Act 1967. Noise-induced hearing loss (NIHL) is the consequences of being exposed to the loud noise at the workplace. Objective: This study was designed to assess the knowledge, attitude and practice (KAP) towards NIHL of quarry workers. Design: A cross sectional study was conducted at 6 quarries in a north-eastern state of Malaysia, with 97 consented respondents who answered a validated version of questionnaire and underwent pure tone audiogram. The respondents were male, aged between 18 to 50-years-old. working in the quarry area for at least 6-month duration and has no family history of ear diseases. Results: The means of percentage score of KAP were 44.3 (10.68), 69.7 (10 .31) and 27.8 (16.05)% respectively and the prevalence of NIHL found to be 56.7% (95% Cl: 46.84, 66.56). There was a significant difference in practice score between workers who had NIHL and non-NIHL (p=0.010). Conclusion: The KAP scores were found to be low in this study and the poor practice was found to have significant difference between the NIHL and non-NIHL, this may lead to the higher prevalence of NIHL in the future without any intervention or awareness program.